> Hi,
>
> Aren't
> def bar(): Long = 3
> and
> def bar: Long = 3
> equivalent?
Seems, they are not, from a type perspective:
scala> def first:Long = 3
first: Long
No parens.
scala> def second():Long = 3
second: ()Long
parens as part of the type.
> Why does the following code snippet compile with a type
> mismatch error (found Long, required () => Long)?
>
> def foo(f: () => Long) = f
> def bar: Long = 3
> foo(bar)
In the last line's expression, 'bar' is evaluated first,
resulting in a Long, which does not match the type of foo's param.
Use by-name parameter to solve this, instead of function type:
scala> def foo (f: => Long ) { println ( f ) }
foo: (=> Long)Unit
----> OK now:
scala> foo(first)
3
----> And even:
scala> foo(second)
3
See PiS page 206 for details
The solution with
def bar(): Long = 3
seems to work, as the type of the expression 'bar' (i.e.: ()=>Long)
matches exactly the expected type of foo's param, so the system assumes
that bar shall not be evaluated first.
> Hi,
>
> Aren't
> def bar(): Long = 3
> and
> def bar: Long = 3
> equivalent?
Seems, they are not, from a type perspective:
scala> def first:Long = 3
first: Long
No parens.
scala> def second():Long = 3
second: ()Long
parens as part of the type.
> Why does the following code snippet compile with a type
> mismatch error (found Long, required () => Long)?
>
> def foo(f: () => Long) = f
> def bar: Long = 3
> foo(bar)
In the last line's expression, 'bar' is evaluated first,
resulting in a Long, which does not match the type of foo's param.
Use by-name parameter to solve this, instead of function type:
scala> def foo (f: => Long ) { println ( f ) }
foo: (=> Long)Unit
----> OK now:
scala> foo(first)
3
----> And even:
scala> foo(second)
3
See PiS page 206 for details
The solution with
def bar(): Long = 3
seems to work, as the type of the expression 'bar' (i.e.: ()=>Long)
matches exactly the expected type of foo's param, so the system assumes
that bar shall not be evaluated first.
KR
Det